Assertiveness as a social and psychological factor of adaptation of migrant women - TSYKALENKO, Olga; VLASOVA, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . Assertiveness is considered to be a significant characteristic of a woman, which determines her ability to effectively interact with the surrounding society on an equal footing and maintain mental health. The article presents a study of assertiveness as a factor in the socio- psychological adaptation of Ukrainian migrant women. The study is based on the hypothesis that there is a positive relationship between the development of assertiveness and the success of social and psychological adaptation of migrant women. It is assumed that the presence of assertiveness in such women is also associated with their higher subjective well-being. M e t h o d s . To obtain empirical data, the following methods were used: "Research of Assertiveness Level" (V. Capponi and T. Novak), Method of Social-Psychological Adaptation by C. Rogers and R. Diamond, "PERMA-Profiler" Questionnaire (Butler and Kern). The SPSS Statistics version 26.0 statistical package and the standard MS Excel program package were used to analyze the obtained data. Descriptive statistics are used to calculate group mean, minimum and maximum values, and standard deviation of mass data. Also applied: Kolmogorov – Smirnov and Shapiro – Wilk criteria, Kruskal-Wallis criterion for independent samples, and Pearson’s correlation coefficient. Sample. 52 Ukrainian women aged 19 to 72 years who, because of the Russian-Ukrainian war, became migrants or ended up in safer regions of Ukraine as internally displaced persons. R e s u l t s . During the study, direct connections of assertiveness as a factor in the organization of the interaction of migrant women with representatives of an unfamiliar environment with the effectiveness of their social and psychological adaptation processes and the level of subjective well-being were statistically confirmed. C o n c l u s i o n s . Assertiveness is a statistically significant factor that helps Ukrainian women, who ended up abroad because of the war, to overcome life challenges associated with a forced change in the social and cultural environment.